Report on the workshop "Organising, Managing and Regulating Martial Arts" during the 21st EASM conference - Vertonghen, Jikkemien; Dortants, Marianne (Revista de Artes Marciales Asiáticas, 2014)
The present report provides a brief account of a workshop entitled “Organising, Managing and Regulating Martial Arts” organised during the 21st EASM conference held in Istanbul (Turkey) on September 12th, 2013. It was the first scientific workshop with regard to the organisational and policy related aspects of (full contact) martial arts. During this international meeting four scientists described in-depth the recent history and current situation regarding the organisation and regulation of martial arts in their country (i.e., France, Flanders (Belgium), Italy and the Netherlands). The workshop was a unique meeting which provided a good opportunity to obtain a better understanding of the specific situation with regard to the regulation of martial arts in some European countries and to exchange results of current research concerning this topic. Further research could be helpful to gain more insight in dealing with problems related to governance, regulation and management of martial arts within a European context.